2003
DOI: 10.3141/1852-16
|View full text |Cite
|
Sign up to set email alerts
|

Toward Benchmarking of Microscopic Traffic Flow Models

Abstract: Several microscopic traffic flow models were tested with a publicly available data set. The task was to predict the travel times between several observers along a one-lane rural road, given as boundary conditions the flow into this road and the flow out of it. By using nonlinear optimization, the best matching set of parameters for each of the models was estimated. For this particular data set, the models that performed best were the ones with the smallest number of parameters. The average error rate of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 13 publications
5
43
3
Order By: Relevance
“…The additional errors in comparison to the calibration are -apart from singular cases of "overfitting" -mainly in the area of 3 to 5 percentage points. The results after the calibration and the validation agree with results that have been obtained before with a completely different data set taking the travel times on road segments instead of headways for the error measurement [14]. In these studies about 15 % to 27 % were found to be the minimum calibration error and additional validation-errors were found to be about 2 to 5 percentage points.…”
Section: Discussionsupporting
confidence: 80%
“…The additional errors in comparison to the calibration are -apart from singular cases of "overfitting" -mainly in the area of 3 to 5 percentage points. The results after the calibration and the validation agree with results that have been obtained before with a completely different data set taking the travel times on road segments instead of headways for the error measurement [14]. In these studies about 15 % to 27 % were found to be the minimum calibration error and additional validation-errors were found to be about 2 to 5 percentage points.…”
Section: Discussionsupporting
confidence: 80%
“…However, the differences or similarities between the published version of the Fritzsche model and the version used in PARAMICS are unknown [20].…”
Section: B Paramicsmentioning
confidence: 99%
“…So, in a final step, it is usually necessary to apply a model with a fitted set of parameters to a different scenario and see how well it fits therewithout adapting the parameters once more. This final step is called validation, and usually the validation results are another 5 per cent worse than the calibration results (Brockfeld et al 2003(Brockfeld et al , 2004(Brockfeld et al , 2005. Within this work, only calibration results will be provided, since a direct comparison between fluid-dynamical and microscopic models is undertaken.…”
Section: (D) Calibration/validation: Optimization Issuesmentioning
confidence: 99%
“…This is not as straightforward as using the speeds since it has to be ensured that no more than the measured flow q sim,out (t) ≤ q out (t) leaves the study area. This can again be reached by an appropriately set speed limit, or by changing the preferred headway of the leading vehicle that slows it down, or, finally, by using a virtual traffic light (Brockfeld et al 2003) that enforces the condition q sim,out (t) ≤ q out (t). However, this causes a strong disturbance in the traffic flow and should be done only if nothing else works, e.g.…”
Section: (C) Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation